2022
DOI: 10.3390/metabo12111026
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Mitochondrial Dysfunction and Impaired Fatty Acid Metabolism in Plasma of Patients with Post-Acute Sequelae of COVID-19 (PASC)

Abstract: Exercise intolerance is a major manifestation of post-acute sequelae of severe acute respiratory syndrome coronavirus infection (PASC, or “long-COVID”). Exercise intolerance in PASC is associated with higher arterial blood lactate accumulation and lower fatty acid oxidation rates during graded exercise tests to volitional exertion, suggesting altered metabolism and mitochondrial dysfunction. It remains unclear whether the profound disturbances in metabolism that have been identified in plasma from patients suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 66 publications
6
88
0
2
Order By: Relevance
“…Many of these findings have been observed in long COVID studies in both adults and children (Box 1). Long COVID research has found mitochondrial dysfunction including loss of mitochondrial membrane potential 105 and possible dysfunctional mitochondrial metabolism 106 , altered fatty acid metabolism and dysfunctional mitochondriondependent lipid catabolism consistent with mitochondrial dysfunction in exercise intolerance 107 , redox imbalance 108 , and exercise intolerance and impaired oxygen extraction 100,109,110 . Studies have also found endothelial dysfunction 29 , cerebral blood flow abnormalities and metabolic changes 81,[111][112][113] (even in individuals with long COVID whose POTS symptoms abate 114 ), extensive neuroinflammation 42,80 , reactivated herpesviruses 18,21,27 , deformed red blood cells 64 Dysautonomia, particularly POTS, is commonly comorbid with ME/CFS 116 and also often has a viral onset 117 .…”
Section: Me/cfs Dysautonomia and Related Conditionsmentioning
confidence: 99%
“…Many of these findings have been observed in long COVID studies in both adults and children (Box 1). Long COVID research has found mitochondrial dysfunction including loss of mitochondrial membrane potential 105 and possible dysfunctional mitochondrial metabolism 106 , altered fatty acid metabolism and dysfunctional mitochondriondependent lipid catabolism consistent with mitochondrial dysfunction in exercise intolerance 107 , redox imbalance 108 , and exercise intolerance and impaired oxygen extraction 100,109,110 . Studies have also found endothelial dysfunction 29 , cerebral blood flow abnormalities and metabolic changes 81,[111][112][113] (even in individuals with long COVID whose POTS symptoms abate 114 ), extensive neuroinflammation 42,80 , reactivated herpesviruses 18,21,27 , deformed red blood cells 64 Dysautonomia, particularly POTS, is commonly comorbid with ME/CFS 116 and also often has a viral onset 117 .…”
Section: Me/cfs Dysautonomia and Related Conditionsmentioning
confidence: 99%
“…Impeding the pathway can cause different disorders (Merritt et al 2018). Very recent studies have observed mitochondrial dysregulation in COVID-19 patient blood cells (Ajaz et al 2021;Guntur et al 2022). Interestingly, the dysfunction of the fatty acid oxidation has been previously connected with fibrosis particularly in the lung and kidney (Geng et al 2021;Jang et al 2020){Merritt, 2018 For the first time, our findings further confirmed that in the fibroblasts, SARS-CoV-2 could induce fibrotic degeneration directly, through down-regulating fatty acid b-oxidation, particularly by the virus' envelope and membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Impeding the pathway can cause different disorders (Merritt et al 2018). Very recent studies have observed mitochondrial dysregulation in COVID-19 patient blood cells (Ajaz et al 2021; Guntur et al 2022). Interestingly, the dysfunction of the fatty acid oxidation has been previously connected with fibrosis particularly in the lung and kidney (Geng et al 2021; Jang et al 2020){Merritt, 2018 #12}.…”
Section: Discussionmentioning
confidence: 99%
“…Next set of features are related to the prediction of treatment stage of the COVID-19 patients. Same analysis on those genes shows that they are closely related to the biological processes such as neutral amino acid transport [95] , regulation of cellular protein metabolic process [84] , negative regulation of cellular macromolecule biosynthetic process [93] , endosome to lysosome transport [50] , chondrocyte morphogenesis involved in endochondral bone morphogenesis, growth plate cartilage chondrocyte morphogenesis, ferrochelatase activity, chondrocyte morphogenesis, phosphatase activator activity [116] , regulation of protein kinase activity [52] , [79] , negative regulation of cellular metabolic process [11] , [8] , response to inorganic substance [111] , [22] , toll-like receptor 9 signaling pathway [1] , [25] , [49] , [70] , [90] , positive regulation of NIK/NF-kappaB signaling [54] , myeloid dendritic cell activation [6] , [85] , regulation of transcription from RNA polymerase II promoter, protein localization to cilium, positive regulation of cell morphogenesis involved in differentiation, mRNA/RNA polyadenylation [102] , [5] , protein localization to cilium, phosphatidylinositol binding, optic cup structural organization [2] , endosome to plasma membrane transport vesicle, SET domain binding, negative regulation of phosphorus metabolic process [110] , regulation of fatty acid transport/ long-chain fatty acid transport [101] , [108] , [32] , [94] , positive regulation of mRNA catabolic process [87] , positive regulation of mRNA metabolic process [54] , transcription from RNA polymerase II promoter, positive regulation of cellular biosynthetic process, negative regulation of RNA metabolic process, negative regulation of nitrogen compound metabolic process [16] , [76] and negative regulation of cellular macromolecule biosynthetic process [30] .…”
Section: Study On the Selected Featuresmentioning
confidence: 99%